A memristive system and its applications in red–blue 3D glasses and image encryption algorithm with DNA variation - Xiong, Li; Yang, Feifei; Mou, Jun; An, Xinlei; Zhang, Xinguo (Nonlinear dynamics, 2022)
In this paper, a memristive circuit system is proposed and its dynamical characteristics are analyzed by two-parameters bifurcation diagrams, Lyapunov exponent spectrum, SE complexity and C0 complexity. The numerical analysis results illustrate that the chaotic state of the memristive system is distributed in a large range of parameters, which is especially suitable for image encryption application. Then, in view of the fact that the traditional method of observing three-dimensional chaotic attractors can not give full play to the essence of human eyes cooperating with brain information processing, a new method to obtain the brain information of complete three-dimensional chaotic attractors by using red–blue 3D glasses is proposed. The results show that compared with the traditional method based on the memristive system, the visual effect of chaotic attractors observed by red–blue 3D glasses is shocking. In addition, an image encryption algorithm is designed to verify the image encryption application of the memristive system based on DNA variation. A series of security performance analysis experiments are performed to verify the effectiveness and reliability of the designed algorithm such as the secret key space analysis, histogram distribution analysis, information entropy analysis, correlation analysis and key sensitivity analysis. Finally, the hardware circuit based on the memristive system is implemented with some common electronic devices, which has the advantages of simple structure and low cost.